STUDY OF MAINTENANCE OF CATTLE BY LIVESTOCK ORIGIN THAT ARE DIFFERENT IN LALEMBUU DISTRICT SOUTH KONAWE DISTRICT - Khaerudin, Khaerudin; Nafiu, La Ode; Arsad Sani, La Ode (Indonesian Journal Of Animal Agricultural Science (IJAAS), 2020)
Beef cattle livestock businesses have an important role in the life of the breeder. Maintenance of beef cattle is generally still done traditionally so that its growth is relatively slow. Beef cattle breeders in the District of Lalembuu come from the origin of the different breeders (Java, Bali, and the Bugis). Based on the preliminary studies it is known that the breeder who originated from different areas has the habits and patterns of different maintenance. Survey and interview method applied to this study involving 60 ranchers respondents. The observed variables are characteristics of respondents, maintenance patterns, system maintenance, maintenance management, business scale, and the outpouring of work (hours of work). The pattern of beef cattle livestock business in district Lalembuu is a pattern of business nurseries. Percentages are based on the original breeders of the Bugis, Javanese, and Balinese is 95%, 90%, and 80%. System maintenance of cattle beef cattle in the District of Lalembuu more dominant done in semi-intensive, with the percentage of each of the original breeders from Bali, Java, and Bugis is 90%, 75%, and 65%. Maintenance management of cattle beef cattle in Lalembuu is a) the ownership of the purchased cattle breeder from Bali is 70%, Java is 55%, Bugis is 50% and the rest using rowdy's system. b) type of feed combination (elephant grass, rice bran, and agricultural waste) provided by the java breeders is 85%, Bali is 70%, Bugis is 65% and the rest use natural grass. c) marital system applied by all breeders are natural breeding. d) The dominant origin of breeders do not perform the treatment against his cattle afflicted by the disease) workflow of the breeder from Bugis, Java, and Bali each is 0,4, 0,44, and 0,46 HOK. The result oh different tests (t-test) showed that there was not significantly different (P>0,05) on workflow from the breeders.Â